Bronchoscopic management of asthma, COPD and emphysema. (13th January 2021) - Perotin, Jeanne Marie; Dewolf, Maxime; Launois, Claire; Dormoy, Valérian; Deslee, Gaëtan
In recent years, many bronchoscopic techniques have been developed in chronic obstructive airway inflammatory diseases, including asthma, COPD and emphysema. The main techniques with available data from randomised controlled trials are: 1) bronchial thermoplasty in asthma; 2) valves, coils and thermal vapor ablation in emphysema; and 3) targeted lung denervation in COPD. The objectives of this article are to describe the levels of evidence for efficacy and safety, long-term follow-up results beyond 1 year, and current recommendations for clinical practice from international guidelines for each technique. Many therapeutic bronchoscopic techniques have been recently developed including bronchial thermoplasty in asthma, and valves, coils and thermal vapor ablation in emphysema, and targeted lung denervation in COPD https://bit.ly/2VhMsDI